A Dynamic North-South Model of Demand-Induced Product Cycles - Reto Foellmi; Sandra Hanslin; Andreas Kohler (FIW - Research Centre International Economics, 2015)
This paper presents a dynamic North-South general-equilibrium model where households have non-homothetic preferences. Innovation takes place in a rich North while norms in a poor South imitate products manufactured in North. Introducing non-homothetic preferences delivers a complete international product cycle as described by Vernon (1966), where the different stages of the product cycle are not only determined by supply side factors but also by the distribution of income between North and South. We ask how changes in Southern labor productivity, South's population size and inequality across regions affects the international product cycle. In line with presented stylized facts about the product cycle we predict a negative correlation between adoption time and per capita incomes.
Keywords: F1; O3; 330; Product cycles; Inequality; International trade